El derecho a la información: balance y cuestiones pendientes - Ortega Gutiérrez, David (Revista de Derecho Político, 2017)
Resumen: Se analiza el derecho a la información y su evolución en estos 40 años de vida de nuestra Constitución de 1978. Primero se estudian aquellas normas jurídicas que han desarrollado directamente este derecho para después ver aquéllas que lo han hecho de manera indirecta o colateral. En segundo lugar apuntamos la evolución jurisprudencial de los temas más relevantes del derecho a la información, especialmente respecto del contenido y límites al mismo. En un tercer apartado se aborda la evolución de la deontología en materia de periodismo. Concluimos con una serie de temas y problemas del derecho a la información que aún siguen pendientes. Summary: 1. Introduction. 2. Normative development. 2.1 Laws that have directly developed the right to information. 2.2 Laws indirectly related to the right to information. 3. Jurisprudential developments. 3.1 Institutional dimension or double character of the right to information, especially against the right to honor. 3.2. Faced with the right to privacy and self-image. 3.3 The right to be forgotten as a limit to the right to information. 3.4 Using the Hidden Camera. 3.5 Legal regulation of radio and television. 3.6 Conscience clause. 3.7 Right to rectification. 3.8 Veracity informative and public relevance of the news. 3.9 Special reference to the ECHR. 4. Journalistic ethics and self-regulation mechanisms. 5. Conclusions and outstanding issues. Abstract: It analyzes the right to information and its evolution in these 40 years of life of our Constitution of 1978. First we study those legal norms that have directly developed this right to later see those who have done so indirectly or collateral. Secondly, we point out the jurisprudential evolution of the most relevant issues of the right to information, especially regarding the content and limits to it. A third section deals with the evolution of deontology in journalism. We conclude with a series of issues and problems of the right to information that are still pending.